Tradisi Mappalili Kabupaten Pinrang : Analisis Sosiologi - Halil, Citra Buana; Angraeni S, Retno (Jurnal JINNSA (Jurnal Interdipliner Sosiologi Agama), 2024)
The Mappalili tradition is a unique tradition of the Bugis tribe which is still often found in society, one of which is in the district. Pinrang, South Sulawesi. This tradition is an activity of praying before entering the rice planting period which is usually carried out by people who work as farmers, with the hope that the harvest will be abundant and agricultural activities will avoid bad things. This activity is identified as a form of ritual that combines cultural and religious values. When people were still trapped under the influence of spiritual power, this ritual usually offered offerings, but since the arrival of Islam, everything has merged into a prayer ritual that is full of Islamic values. This article tries to redescribe the practices of the Mappalili tradition and examine the beginnings of this tradition developing in the district community. Pinrang utilizes previously existing writings using library research, which is then analyzed using Bourdieu's theory of practice. The results of the literature analysis show that the Mappalili tradition is carried out in three main processes, namely: tudang sipulung, Mabukka tana, Manre Sipulung, the Mappalili procession describes the sacred value of Durkheim who considers that this ritual is a sacred thing and can have bad consequences if it is not carried out, besides that it was found that If you look at it using Bourdieu's analysis, this tradition is a complementary strategy to other physical efforts that have been carried out by farmers, meaning that there is an approach to the Almighty Creator to get good results in increasing capital with material value.